Inovasi dalam Pendidikan Berbasis Life Skills di Pondok Pesantren Modern Darul Ma’rifat Deli Serdang - manshuruddin, Manshuruddin; Yunan Harahap, Muhammad; Sandhya, M. Bayu (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study examines innovations in life skills-based education implemented at the Darul Ma'rifat Modern Islamic Boarding School in Deli Serdang. The main focus of this study is to explore the methods, strategies, and educational programs implemented to improve the life skills of students. The research method used is a qualitative approach with in-depth interviews, non-participatory observation, and documentation studies. The results of the study indicate that this Islamic boarding school integrates religious education with life skills through a curriculum that involves daily activities, such as congregational prayer, entrepreneurship training, and vocational and social skills. This approach not only improves the academic skills of students but also prepares them with practical skills that are relevant to the demands of the modern world. The implications of these findings indicate that the integration of religious education with life skills is an effective strategy to create students who are independent, adaptive, and ready to face social and economic challenges in the future.